2012
DOI: 10.1083/jcb.201110135
|View full text |Cite
|
Sign up to set email alerts
|

Fascin promotes filopodia formation independent of its role in actin bundling

Abstract: Mutation of a critical residue of fascin eliminates the protein’s actin-bundling activity but maintains its positive role in filopodia formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 35 publications
7
119
0
Order By: Relevance
“…6D,E; supplementary material Movies 10, 11). These results are consistent with a correlation between the activity, accumulation and phosphorylation state of Sn (Nagel et al, 2012;Zanet et al, 2012).…”
Section: S52asupporting
confidence: 79%
See 1 more Smart Citation
“…6D,E; supplementary material Movies 10, 11). These results are consistent with a correlation between the activity, accumulation and phosphorylation state of Sn (Nagel et al, 2012;Zanet et al, 2012).…”
Section: S52asupporting
confidence: 79%
“…However, in in vivo systems such as Drosophila, phosphorylation on S52 inactivates sn activity in certain conditions but not in others (Zanet et al, 2009). Furthermore, although it is widely accepted that fascins act as actin-bundling proteins, a recent report proposed a bundling-independent activity of fascins that promote filopodia formation (Zanet et al, 2012).…”
Section: Molecular Requirements For Sn During Tracheal Formationmentioning
confidence: 99%
“…Transcriptional profiling studies suggest that Drosophila Kc167 cells are plasmatocytes (Cherbas et al 2011), a subclass of hemocytes involved in immune surveillance that may further differentiate into lamellocytes, podocytes, or macrophages (Stofanko et al 2010). To examine whether ecdysone tRNA levels and protein translation www.rnajournal.org 1809 treatment has an effect on the differentiation state of Kc167 cells, we analyzed expression markers for these relevant cell types at 0, 3, and 48 h. Up-regulation of Croquemort, a macrophage receptor for apoptotic cells (Franc et al 1996(Franc et al , 1999, Singed (Fascin), an actin-bundling protein important for macrophage migration (Zanet et al 2012), and Schnurri, previously shown to regulate hemocyte-to-macrophage differentiation (Kelsey et al 2012), together suggest that ecdysone induces plasmatocyte-to-macrophage differentiation in this cell line (Fig. 3A).…”
Section: Transcriptional and Proteomic Response To Steroidhormone Sigmentioning
confidence: 99%
“…For domain analysis, UAS-GFPmoesin (Dutta et al, 2002) or UASLifeActGFP (Zanet et al, 2012) was driven in haemocytes to label actin, and cells were visualised for 2 hours at 1-minute intervals. The time-lapse series was then thresholded within ImageJ (NIH) and flattened with an average intensity projection.…”
Section: Domain Analysismentioning
confidence: 99%